Community Empowerment: Ecobrick Training as a Sustainable Solution to Plastic Waste Management on Banten's Panjang Island - Rayhan, Ahmad; Nurikah, Nurikah; Jazuli, E. Rakhmat (Probono and Community Service Journal, 2024)
Panjang Island is one of the islands in Banten Regency, which has problems related to plastic waste. Plastic waste is also a major problem in environmental pollution in Indonesia and the world, so there is a need for a way or method that can reduce plastic waste in the region. One effort or method that can be done to deal with plastic waste is with ecobricks or environmentally friendly bricks. Ecobrick comes from the words ecology which means ecology and brick which means brick or can also be called environmentally friendly brick. The method used is Ecobrick Training and Training, this activity was carried out on August 5 2023 in Pulau Panjang Village, Pulau Ampel District, Serang Regency. The Ecobrick training was attended by representatives of young people from the Panjang Island Village Youth Organization. This training activity was carried out in 2 steps, namely presentation of material on the negative impacts of plastic waste and practice of making ecobricks. This activity is carried out in several stages, namely preparation, implementation and post-training. The aim of the ecobrick making training activity is to provide education and assistance regarding environmentally friendly plastic waste processing. Based on the results of training activities and Ecobrick Training, it is known that young people from Karang Taruna are able to manage plastic waste using the ecobrick method. It is hoped that Karang Taruna youth will not only be able to process plastic waste into ecobricks but can also use it as a field for creativity.